Primary Nasal Epithelial Cells as a Surrogate Cell Culture Model for Type-II Alveolar Cells to Study ABCA-3 Deficiency - Shaw, Nicole C.; Kicic, Anthony; Fletcher, Sue; Wilton, Stephen D.; Stick, Stephen M.; Schultz, André (Frontiers in Medicine, 2022)
ATP Binding Cassette Subfamily A Member 3 (ABCA-3) is a lipid transporter protein highly expressed in type-II alveolar (AT-II) cells. Mutations in ABCA3 can result in severe respiratory disease in infants and children. To study ABCA-3 deficiency in vitro, primary AT-II cells would be the cell culture of choice although sample accessibility is limited. Our aim was to investigate the suitability of primary nasal epithelial cells, as a surrogate culture model for AT-II cells, to study ABCA-3 deficiency. Expression of ABCA3, and surfactant protein genes, SFTPB and SFTPC, was detected in primary nasal epithelial cells but at a significantly lower level than in AT-II cells. ABCA-3, SP-B and SP-C were detected by immunofluorescence microscopy in primary nasal epithelial cells. However, SP-B and SP-C were undetectable in primary nasal epithelial cells using western blotting. Structurally imperfect lamellar bodies were observed in primary nasal epithelial cells using transmission electron microscopy. Functional assessment of the ABCA-3 protein demonstrated that higher concentrations of doxorubicin reduced cell viability in ABCA-3 deficient nasal epithelial cells compared to controls in an assay-dependent manner. Our results indicate that there may be a role for primary nasal epithelial cell cultures to model ABCA-3 deficiency in vitro, although additional cell culture models that more effectively recapitulate the AT-II phenotype may be required.